Choreographic Process of the Batik Ponoragan Dance in the Work Larastika Larang - Lilik Sunarti; Ni Nyoman Yuliarmaheni (Jurnal Seni Tari, 2025)
This study This study explores the choreographic process of Tari Batik Ponoragan as an artistic response to the local culture of Ponorogo, particularly through the integration of Reog batik motifs into contemporary dance performance. Developed under the Larastika Larang collaborative project, the work applies a practice-led research approach, in which artistic practice serves as the primary method for producing knowledge and cultural reflection. The choreographic process is based on Alma M. Hawkins’ theory, consisting of three stages: exploration, improvisation, and composition. Through exploration, dancers interpreted batik-making gestures and Reog symbols into movement. The improvisation stage allowed the body to respond spontaneously to visual, auditory, and emotional stimuli. In the composition stage, the findings were arranged into a three-part choreographic structure: batik production, its connection to local arts, and the collaborative conclusion. Findings indicate that dance can serve as a medium for cultural revitalization through reflective and participatory methods. The work not only presents aesthetic values but also offers a contemporary narrative of cultural identity and memory within the Ponorogo community.